Violence as a Subject of Social Science I The Specificity of Political Violence - Mario Domínguez Sánchez-Pinilla; Isis Sánchez Estellés (Budapest International Research and Critics University, 2021)
In contrast to the world's uniformity all types of violence are observed: urban violence, in poor countries where conflicts are incomprehensible from outside, violence which surface is religious in countries of Muslim tradition, fundamentalist violence, nationalist, racist; violence in the world system which accepts the growing difference between poor and rich. Judiciary violence in executions in States that seem the principal warrantors of social peace. There is violence throughout the globe and under surveillance by the great power. It could be said that the global system tolerates a certain “reserve of violence” and obtains certain profits, as well as the economy tolerates certain extent of “unemployment rate” able to calm protest movements.